Pathogenesis of acute hepatopancreatic necrosis disease (AHPND) in shrimp. Issue 2 (December 2015) - Lai, Hung-Chiao; Ng, Tze Hann; Ando, Masahiro; Lee, Chung-Te; Chen, I-Tung; Chuang, Jie-Cheng; Mavichak, Rapeepat; Chang, Sheng-Hsiung; Yeh, Mi-De; Chiang, Yi-An; Takeyama, Haruko; Hamaguchi, Hiro-o; et al.
Abstract: Acute hepatopancreatic necrosis disease (AHPND), also called early mortality syndrome (EMS), is a recently emergent shrimp bacterial disease that has resulted in substantial economic losses since 2009. AHPND is known to be caused by strains of Vibrio parahaemolyticus that contain a unique virulence plasmid, but the pathology of the disease is still unclear. In this study, we show that AHPND-causing strains of V. parahaemolyticus secrete the plasmid–encoded binary toxin PirAB vp into the culture medium. We further determined that, after shrimp were challenged with AHPND-causing bacteria, the bacteria initially colonized the stomach, where they started to produce PirAB vp toxin. At the same early time point (6 hpi), PirB vp toxin, but not PirA vp toxin, was detected in the hepatopancreas, and the characteristic histopathological signs of AHPND, including sloughing of the epithelial cells of the hepatopancreatic tubules, were also seen. Although some previous studies have found that both components of the binary PirAB vp toxin are necessary to induce a toxic effect, our present results are consistent with other studies which have suggested that PirB vp alone may be sufficient to cause cellular damage. At later time points, the bacteria and PirA vp and PirB vp toxins were all detected in the hepatopancreas. We also show that Raman spectroscopy "Whole organism fingerprints" were unable to distinguish between AHPND-causing and non-AHPND causing strains. Lastly, by using minimum inhibitory concentrations, we found that both virulent and non-virulent V. parahaemolyticus strains were resistant to several antibiotics, suggesting that the use of antibiotics in shrimp culture should be more strictly regulated. Highlights: AHPND-causing Vibrio parahaemolyticus secrete the binary toxin PirAB vp into the culture medium. PirAB vp proteins were detected in the stomach and hepatopancreas. Both virulent and non-virulent V. parahaemolyticus strains were resistant to several antibiotics.